Pengaruh Pembelajaran Pendidikan Agama Islam Terhadap Perilaku Asertif Siswa Kelas VII A SMP Al-Amaanah Tasikmadu - Hasyim Asy’ Ari; Nur Hidayah; Yunan Hidayat (Journal on Education, 2023)
This study aims to determine whether there is an influence between learning Islamic Religious Education on Assertive behavior of class VII A students at SMP AL-AMAANAH Tasikmadu. Islamic Religious Education Learning is a systematic process that aims to develop understanding and awareness of Islamic religious teachings and practices. Assertive behavior is an attitude and way of interacting with others that is characterized by clear, firm and straightforward self-expression, while still respecting the rights and feelings of others. This study uses a correlational quantitative method. The population in this study were 32 class VII A students at SMP AL-AMAANAH Tasikmadu. Collecting data in this study by questionnaire method. While the data analysis technique in this study used descriptive analysis techniques which were processed using SPSS software. The results showed that (1) the learning of Islamic Religious Education at SMP AL-AMAANAH Tasikmadu was proven by analyzing the questionnaire, which consisted of 32 respondents in the medium category, namely 62.5%. (2) Assertive behavior as evidenced by analyzing the questionnaire, which totaled 32 respondents were in the medium category, namely 65.6% (3) There was a very strong influence between learning Islamic Religious Education on Assertive behavior of class VII A students at AL-AMAANAH Middle School Tasikmadu. This is known from the results of the Pearson correlation test of 0.821 > 0.05 and it is at a very strong level of relationship, namely at the criterion number 0.75 to 0.99..